Sensorimotor and Executive Function Slowing in Anesthesiology Residents After Overnight Shifts. Issue 5 (October 2017) - Williams, G. W.; Shankar, B.; Klier, E. M.; Chuang, A. Z.; El Marjiya-Villarreal, S.; Nwokolo, O. O.; Sharma, A.; Sereno, A. B.
Abstract : (Abstracted from J Clin Anesth, 40:110–116, 2017) Physicians and medical residents working overnight shifts suffer from sleep deprivation, cognitive dysfunction, and decreased sensorimotor performance due to disturbances in circadian rhythms. This can lead to medical errors and work-related injuries and accidents.